Aplikasi Mobile Advertising Berbasis Location Based Service (LBS) Untuk Kafe Di Pekanbaru - Nabilah Nasution; Mardhiah Fadhli; Dini Nurmalasari (UIN Sultan Syarif Kasim Riau, 2015)
Spread manifold cafe coffee shop making cafe owners competing to promote their cafe. Advertising is one of the efforts that can be done to increase the sale value, attracting consumers as well as to promote a cafe. As the development of technology, advertising began to be developed through mobile technology. Advertising is done through mobile technology is called Mobile Advertising. However, the ads that appear on the application it can annoy users. Therefore, mobile advertising application is made by the ads that appear when there is a request from the user. The application also uses location technology based services that can provide location information of a cafe. Based on the test results through questionnaires obtained an average of 88.8% of users said that the mobile application advertising-based location based service for a cafe in Pekanbaru can provide advertising and information of a cafe as well as provide information about the location of the cafe accurate than the user's position making it easier for users to perform search. Android-based application is built using Eclipse with Java programming language.Keywords: android,coffee shop, location based services, mobile advertising.